Accelerated Discovery in Photocatalysis using a Mechanism‐Based Screening Method. Issue 13 (11th March 2016) - Hopkinson, Matthew N.; Gómez‐Suárez, Adrián; Teders, Michael; Sahoo, Basudev; Glorius, Frank
Abstract: Herein, we report a conceptually novel mechanism‐based screening approach to accelerate discovery in photocatalysis. In contrast to most screening methods, which consider reactions as discrete entities, this approach instead focuses on a single constituent mechanistic step of a catalytic reaction. Using luminescence spectroscopy to investigate the key quenching step in photocatalytic reactions, an initial screen of 100 compounds led to the discovery of two promising substrate classes. Moreover, a second, more focused screen provided mechanistic insights useful in developing proof‐of‐concept reactions. Overall, this fast and straightforward approach both facilitated the discovery and aided the development of new light‐promoted reactions and suggests that mechanism‐based screening strategies could become useful tools in the hunt for new reactivity. Abstract : Enlightened ! A mechanism‐based screening approach can accelerate discovery in photocatalysis. It focuses on a single mechanistic step of a reaction class: the quenching step central to photocatalytic transformations. Luminescence spectroscopy was used to screen 100 compounds, identifying two promising substrate classes. A second, more‐focused screen provided mechanistic insights for developing proof‐of‐concept reactions.